Prolonged grievers: A qualitative evaluation of a support group intervention. Issue 4 (8th August 2013) - Friedrichsen, Maria; Hajradinovic, Yvonne; Jakobsson, Maria; Sundberg, Lars; Jonsson, Monica Axmacher; Milberg, Anna
Abstract Objective: The aim of this project was to study prolonged grievers psychosocial processes and experience during participation in a group intervention and 6–8 weeks after discontinuation. The intervention in this study was a group therapy with the aim of getting in contact with their pain and loss and confronting and working with this loss. Methods: Data was collected by using diaries and tape-recorded interviews, analyzed with grounded theory. The participants were 11 females between the ages of 33 and 71. Results: The main process that was found in the qualitative data was: Ambivalence when struggling and learning through work and rest towards a balance. Sub-processes were: To share and be confirmed in the group through sense of cohesion; To dare/venture to discover problems and solutions; To react when you get emotionally involved, and to compare and discover. Significance of results: This study gives insight into prolonged grievers' thinking, which is valuable knowledge. Rather than assuming that all individuals suffering from prolonged grief need the same treatment, we suggest that there should be a range of different therapies.